Analisa Dan Perancangan Sistem Rekrutmen Guru Les Bahasa Inggris Dengan Metode Promethee Berbasis Website - Akram Maiklen; Perani Rosyani (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
The recruitment process for qualified English teachers presents a significant challenge for educational institutions, especially when there are many candidates with diverse backgrounds and criteria. The Indonesia America Education Institute (LPIA) is required to conduct the teacher selection process objectively, systematically, and efficiently to obtain teaching staff that meet institutional needs. This study aims to develop a web-based Decision Support System (DSS) using the Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) method, which assists in determining the ranking of the best teacher candidates based on several assessment criteria, namely English proficiency, communication skills, educational background, teaching experience, and age. The results of the study indicate that the developed system is capable of processing candidate data, calculating preference values, and automatically generating final ranking results based on Net Flow values. Thus, the system helps LPIA make recruitment decisions more quickly, accurately, and in a well-documented manner. The implementation of the PROMETHEE method has proven effective in supporting the teacher selection process at LPIA, which was previously carried out manually.